STRATEGI KOMUNIKASI POLITIK PARTAI GOLONGAN KARYA (GOLKAR) DALAM PEMILU LEGISLATIF TAHUN 2019 DI KABUPATEN KUANTAN SINGINGI - Syofian, Ridho; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In the legislative general election which took place in Kuantan Singingi Regency in the period 2019-2023 the Regional Representative Council of the Kuantan Singingi District conducted a new legislative election, where the election was held at the constituency. Of the many party factions that participated in the legislative elections, the Golkar faction received the most votes. The Golkar faction won the most votes with 6 seats in the legislature. Likewise, the legislative election in the 2014-2019 period, the Golkar faction also won the legislative election by successfully sending 9 cadres to the legislative seats. This study aims to determine the political communication strategy of the Golkar Party in Kuantan Singingi Regency in winning the 2019 legislative elections, and also to find out what political marketing programs are being run.This study used qualitative research methods. Data collection techniques are grouped into three parts, namely: Observation, interview, and documentation. The subjects in this study consisted of 6 research subjects, consisting of 3 people representing the Golkar DPD secretariat in Kuantan Singingi Regency as informants through purposive sampling techniques, and 3 people from the community representing voter segmentation. The data analysis techniques in this study use the Miles and Huberman interactive data models. Checking the validity of the data using the technique of extending participation and triangulation.From the results of this study it was found that the political communication strategy undertaken by the Golkar Party DPD in Kuantan Singingi Regency to win the 2019 legislative election was to determine Planning (planning), starting from determining the communicator, the message to be conveyed, the use of the media, determining the audience, and the effect is expected. Implementation (action), and Assessment (evaluation). Political marketing of Golkar includes (1) Party products, namely a platform as a party that continues to support the ideology of the unitary state of the Republic of Indonesia, (2) Promotion through various mass media and direct selling, (3) Places that follow the KPU's direction (4) Price consisting of economic and psychological prices. Then the targets of political marketing are housewives, students, and farmers. Keyword: Strategy, Communication Strategy of Political, legislative 2019